(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2017)
Need for large quantity of bacterial cellulose (BC), used as a matrix for production of numerous materials with desirable properties, has increased in the fields of biomedicine and electronics. To achieve the goals further investigations are essential in order to understand the intracellular polymerisation reaction; to increase the biosynthesis rate and reduce cost of the overall production process. Carbon sources for the BC production are usually glucose, fructose, and sucrose, so juices from low grade fruits can successfully substitute the carbohydrates, vitamins, ascorbic acid, and proteins in the growth medium and can form low-cost substrates. We used strain Gluconoacetobacter xylinus CICC10529 to produce cellulose from watermelon and mandarin juices (70% v/v and 80% v/v) with or without yeast extract supplement. The liquid media (with working volumes 50 mL and 100 mL) made from fruit juices always contained MgSO4.7H2O (1.5 w/v%), K2HPO4 (0.1 w/v%), as well as ethanol (1 v/v%). Two modes of operation: static biosynthesis in incubator and dynamic biosynthesis in orbital shaker (at 200 rpm) were conducted at 30°C. The production process was monitored during 7 to 10 days. Thermal properties of BC produced at different conditions were investigated through thermal gravimetric analysis and width of the cellulose fibrils/ribbons were compared via microscopic observations.